EFL Students’ Perception Towards Kahoot! as A Gamification Tool in English Learning - Zulfa, Adelia Oktaviana (Universitas PGRI Semarang, 2024)
Technology in education forces teachers to modify their teaching strategies by implementing gamification as a tool in teaching and learning process. Kahoot is a popular gamification tool in English learning. Using a qualitative research design, this study aimed to determine the EFL students' perception of the gamification tool in an English learning environment. Thirty-six (36) students of 10th grade from a public senior high school in Semarang, Central Java, Indonesia. The participants were asked to complete a closed-ended questionnaire using Google Forms to gain information about their perceptions of the educational environment. The findings revealed that the students generally have a positive perception of Kahoot! as a gamification tool in the English learning process. The interactive and competitive nature of the quizzes increases students' motivation and engagement in the learning process, which can enhance students' engagement and motivation in the classroom. The students generally perceive Kahoot! as an effective, fun, and effective educational environment that enhances students' learning experience and creates a vibrant and engaging classroom environment. By combining motivation, collaboration, competition, fun, interest, excitement, and an energetic environment, Kahoot! can enhance the English learning experience, promote interaction and collaboration, and offer customizable features.